MODERN METHODOLOGICAL AND FUNCTIONAL APPROACHES TO DEVELOPING LONG JUMP TECHNIQUE - Yigitaliyev Abubakir Farxodjon o‘g‘li (Modern World Education: New Age Problems – New solutions, 2025)
This article examines methods for developing the functional capacities of track-and-field athletes, with a particular focus on the long jump. The study analyzes a training system aimed at improving athletes’ overall physical preparedness and key motor qualities such as speed, strength, and endurance. In addition, the article substantiates the necessity of enhancing technical and functional performance indicators through the rational selection of exercises, appropriate load regulation, and systematic pedagogical control.